1999
DOI: 10.1038/sj.ijo.0800801
|View full text |Cite
|
Sign up to set email alerts
|

A study in the relationships between leptin, insulin, and body fat in Asian subjects

Abstract: OBJECTIVE: To study the relationship of leptin concentrations with indices of obesity, fasting insulin, insulin resistance and lipid pro®les (total cholesterol, low density lipoprotein (LDL)-cholesterol, high density lipoprotein (HDL)-cholesterol and triglyceride) in an Asian cohort. DESIGN: Cross sectional study. SUBJECTS: A total of 133 healthy volunteers were enrolled (64 female: age: 25 ± 61 y, body mass index (BMI): 18.7 ± 45.1 kgam 2 and 69 male: age: 25 ± 61 y, BMI: 19.3 ± 35.0 kgam 2 ). MEASUREMENTS: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 48 publications
3
13
0
1
Order By: Relevance
“…Haluzik et al [23] reported that the plasma leptin level and lipid profile is different in healthy and hyperlipidemic children. In adults only a poor relationship was noted between leptin levels and the lipid profile [26,27]. We did not find a cor-relation between serum leptin levels and total cholesterol, HDL cholesterol, LDL cholesterol, and TG levels in marasmic children, but a positive correlation was found between leptin and HDL cholesterol levels and a negative correlation with LDL cholesterol levels in females and a positive correlation with LDL cholesterol levels in males.…”
Section: Discussionmentioning
confidence: 52%
“…Haluzik et al [23] reported that the plasma leptin level and lipid profile is different in healthy and hyperlipidemic children. In adults only a poor relationship was noted between leptin levels and the lipid profile [26,27]. We did not find a cor-relation between serum leptin levels and total cholesterol, HDL cholesterol, LDL cholesterol, and TG levels in marasmic children, but a positive correlation was found between leptin and HDL cholesterol levels and a negative correlation with LDL cholesterol levels in females and a positive correlation with LDL cholesterol levels in males.…”
Section: Discussionmentioning
confidence: 52%
“…Percentage body fat was calculated from the formula [(weight 7 lean body mass)a weight]Â100%. In a previous study, 18 the coef®cient of variation (CV) for total fat mass determined by repeated measurement in six individuals within 3 days was 4.7%. The formulae for measurement of percentage body fat in Western populations using bioelectric impedance analysis have been shown to apply in Chinese, which make up the majority of our study population.…”
Section: Methodsmentioning
confidence: 99%
“…It appears that plasma leptin is associated with peripheral rather than central obesity when measured by anthropometry in our population. 18 This study allows us to con®rm these ®ndings and determine the relationship between visceral fat and plasma leptin concentration.…”
Section: Introductionmentioning
confidence: 99%
“…64,65 Serum leptin increases in parallel with BMI and, interestingly, is higher in women. [66][67][68][69][70] The sexual dimorphism in circulating leptin levels is apparent already in childhood 71,72 and has been attributed to differences in subcutaneous fat mass and adipocyte cell size. 73,74 But could gender differences in body fat distribution be indicative of a differential leptin production between depots?…”
Section: Leptinmentioning
confidence: 99%